Pengaruh Beban Kerja, Stres Kerja, dan Work-Life Balance terhadap Kepuasan Kerja serta Dampaknya pada Organizational Citizenship Behavior - Regina Yusticia Firdaus; Herma Wiharno; Lili Karmela Fitriani (Jurnal Syntax Admiration, 2024)
In achieving success for a company/organization, human resources are one of the most important assets. Employees are not only required to be able to carry out work according to their duties, but employees are also required to have abilities outside of their duties which is called Organizational Citizenship Behavior. This research aims to analyze the influence of workload, work stress, and work-life balance on job satisfaction and its impact on organizational citizenship behavior (Study at PT. Global Jet Express, East Cirebon Region). The type of research used in this research is quantitative research with descriptive and verification methods, and the total sample was 288 employees of PT Global Jet Express in the East Cirebon Region with using non-probability sampling techniques. The analysis tool used is Structural Equation Modeling (SEM) with the help of the SmartPLS 4.0 program. The results of the research show that workload and work stress have no effect on job satisfaction or Organizational citizenship behavior, work-life balance and job satisfaction have a positive effect on job satisfaction and Organizational citizenship behavior, job satisfaction is not able to mediate between workload and Organizational citizenship behavior, job satisfaction unable to mediate between work stress Organizational citizenship behavior, and job satisfaction able to mediate between work-life balance and Organizational citizenship behavior.